Managing circular ecosystems in imperfect contexts – the case of extractive fishing in the Brazilian Amazon region - Neuzaí Marreiros Barbosa; Pedro Ibrahim Hellmeister; Adriana Marotti De Mello; Antonio Carlos Braz (RAUSP Management Journal)
Purpose – This study aims to answer the question of how to structure a circular ecosystem for extractive fishing in the Amazon region. It explores possibilities for implementing a circular ecosystem management model in an imperfect market with low technological availability, high informality and limited public assistance. Design/methodology/approach – Qualitative approach was adopted for this paper, with a case study on extractive fishing in the state of Amazonas. Data was collected through 35 interviews and direct observation of the processes of collecting, storing and transporting fish on two routes: Tapauá-Manaus and Manacapuru-Manaus. Findings – Through the data collected, it was possible to observe the importance of an orchestrating agent – such as an association or even a public authority – for the establishment and development of a circular ecosystem for extractive fishing in the region. Research limitations/implications – The paper makes theoretical contributions by presenting how a circular ecosystem management model could be implemented for an imperfect market in the Global South, as well as contributing to the literature on how the circular economy contributes to mitigate the threat to biodiversity posed by the linear economy. Practical implications – It contributes to the management practice of structuring circular ecosystems. Social implications – The role of public authorities and the collective organization of fishermen as orchestrators connecting the network of actors that develop the extractive fishing ecosystem is fundamental, guaranteeing effective social participation in solving local problems. Originality/value – The idea of circular ecosystems was applied to imperfect contexts, with high informality, weak institutions and bioeconomy, topics still little explored in the literature.